Dynamics of Waste Accumulation: Disposal Versus Recycling - Smith, Vernon L. (Quarterly Journal of Economics, 1972)
Introduction, 600. — A model of waste reuse, 601. — Prices in the control model, 605. — Conditions for complete and zero recycling, 607. — Pollution under free competition, 608. — Effects of population, 611. — Interpretation as a waste reduction model, 612. — Material production from natural resources, 612. — Summary and discussion of policy, 614.